Nested Spheres and n-gonal Prisms

Level pending

Let n > = 4 n >= 4 be a fixed positive integer and consider an n n -gonal prism whose bases are regular n n gons and faces are congruent rectangles.

For each positive integer m m ,

Let V c ( m ) V_{c}(m) be the volume of the largest n n -gonal prism that can be inscribed in a sphere of volume V s ( m ) V_{s}(m)

Let V s ( m + 1 ) V_{s}(m + 1) be the volume of the largest sphere that be inscribed in the n n -gonal prism of volume V c ( m ) V_{c}(m) .

Let V s ( n ) = m = 1 V s ( m ) V^{*}_{s}(n) = \sum_{m = 1}^{\infty} V_{s}(m) and V c ( n ) = m = 1 V c ( m ) V^{*}_{c}(n) = \sum_{m = 1}^{\infty} V_{c}(m) and let the volume of the initial sphere V s ( 1 ) = 1 V_{s}(1) = 1 .

Find: lim n V s ( n ) V c ( n ) \lim_{n \rightarrow \infty} V^{*}_{s}(n) * V^{*}_{c}(n) , and express the result to five decimal places.

Note: My intention is not to reduce the problem to nested spheres and right circular cylinders, but you will get the correct result if you do so., since lim n V c ( n ) = V c y l i n d e r \lim_{n \rightarrow \infty} V_{c}(n) = V_{cylinder} , where V c ( n ) V_{c}(n) is the volume of a n n -gonal prism.


The answer is 2.78061.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 9, 2017

For area of n g o n n - gon :

Let B C = x BC = x be a side of the n g o n n - gon , A C = A B = r AC = AB= r^{*} , A D = h AD = h^* , and B A D = π n \angle{BAD} = \dfrac{\pi}{n} .

x 2 = r sin ( π n ) r = x 2 sin ( π n ) h = r cos ( π n ) \dfrac{x}{2} = r^{*} \sin(\dfrac{\pi}{n}) \implies r^{*} = \dfrac{x}{2 \sin(\dfrac{\pi}{n})} \implies h^{*} = r^{*} \cos(\dfrac{\pi}{n}) \implies

A n g o n = n 2 sin ( 2 π n ) r 2 A_{n - gon} = \dfrac{n}{2} \sin(\dfrac{2\pi}{n}) {r^{*}}^2 \implies The volume of the n n -gonal prism is V c = n 2 sin ( 2 π n ) r 2 H V_{c} = \dfrac{n}{2} \sin(\dfrac{2\pi}{n}) {r^{*}}^2 H

Let H H be the height of the given n g o n a l n-gonal prism.

In the right triangle above: A C = H 2 , B C = r , A B = R AC = \dfrac{H}{2}, BC = r^{*}, AB = R \implies

r 2 = 4 R 2 H 2 4 V p ( H ) = n 8 sin ( 2 π n ) ( 4 R 2 H H 3 ) d V c d H = n 8 sin ( 2 π n ) ( 4 R 2 3 H 2 ) = 0 H = 2 R 3 {r^{*}}^2 = \dfrac{4 R^2 - H^2}{4} \implies V_{p}(H) = \dfrac{n}{8} \sin(\dfrac{2\pi}{n}) (4R^2 H - H^3) \implies \dfrac{dV_{c}}{dH} = \dfrac{n}{8} \sin(\dfrac{2\pi}{n}) (4 R^2 - 3 H^2) = 0 \implies H = \dfrac{2R}{\sqrt{3}} \implies

r 2 = 2 3 R 2 r = 2 3 R V c ( 1 ) = n 2 3 π sin ( 2 π n ) V s ( 1 ) {r^{*}}^2 = \dfrac{2}{3} R^2 \implies r^{*} = \sqrt{\dfrac{2}{3}} R \implies V_{c}(1) = \dfrac{n}{2\sqrt{3}\pi} \sin(\dfrac{2\pi}{n}) V_{s}(1)

For the inscribed sphere:

The radius of the inscribed sphere r = h = r cos ( π n ) = 2 3 cos ( π n ) R V s ( 2 ) = 2 3 2 3 cos 3 ( π n ) V s ( 1 ) r = h^{*} = r^{*} \cos(\dfrac{\pi}{n}) = \sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}) R \implies V_{s}(2) = \dfrac{2}{3} \sqrt{\dfrac{2}{3}} \cos^{3}(\dfrac{\pi}{n}) V_{s}(1)

Let r 1 = R , r 2 = r = r cos ( π n ) = 2 3 cos ( π n ) R , r 1 = 2 3 R , H 1 = 2 3 R r_{1} = R, \:\ r_{2} = r = r^{*} \cos(\dfrac{\pi}{n}) = \sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}) R, \:\ r_{1}^{*} = \sqrt{\dfrac{2}{3}} R, \:\ H_{1} = \dfrac{2}{\sqrt{3}} R \implies

r 2 = 2 3 r 2 = 2 3 ( 2 3 cos ( π n ) ) R r_{2}^{*} = \sqrt{\dfrac{2}{3}} r^2 = \sqrt{\dfrac{2}{3}} (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n})) R

H 2 = 2 3 ( 2 3 cos ( π n ) ) R H^{2} = \dfrac{2}{\sqrt{3}} (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n})) R

r 3 = ( 2 3 cos ( π n ) ) 2 R r_{3} = (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^2 R

r 3 = 2 3 ( 2 3 cos ( π n ) ) ) 2 R r_{3}^{*} = \sqrt{\dfrac{2}{3}} (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n})))^2 R

H 3 = 2 3 ( 2 3 cos ( π n ) ) 2 R H_{3} = \dfrac{2}{\sqrt{3}} (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^2 R

In General:

r ( m ) = ( 2 3 cos ( π n ) ) m 1 R r(m) = (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^{m - 1} R

r ( m ) = 2 3 ( 2 3 cos ( π n ) ) m 1 R r^{*}(m) = \sqrt{\dfrac{2}{3}} (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^{m - 1} R

H ( m ) = 2 3 ( 2 3 cos ( π n ) ) m 1 R H(m) = \dfrac{2}{\sqrt{3}} (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^{m - 1} R

V c ( m ) = n 2 3 π sin ( 2 π n ) ( 2 3 cos ( π n ) ) 3 ( m 1 ) V s ( 1 ) \implies V_{c}(m) = \dfrac{n}{2\sqrt{3} \pi} \sin(\dfrac{2\pi}{n}) (\dfrac{2}{3} \cos(\dfrac{\pi}{n}))^{3(m - 1)} * V_{s}(1) and V s ( m ) = ( 2 3 cos ( π n ) ) 3 ( m 1 ) V s ( 1 ) V_{s}(m) = (\dfrac{2}{3} \cos(\dfrac{\pi}{n}))^{3(m - 1)} * V_{s}(1) \implies

V c ( n ) = m = 1 V c ( m ) = n 2 3 π sin ( 2 π n ) ( 1 1 ( 2 3 cos ( π n ) ) 3 ) V^{*}_{c}(n) = \sum_{m = 1}^{\infty} V_{c}(m) = \dfrac{n}{2\sqrt{3}\pi} \sin(\dfrac{2\pi}{n}) (\dfrac{1}{1 - (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^3}) and V s ( n ) = ( 1 1 ( 2 3 cos ( π n ) ) 3 ) V^{*}_{s}(n) = (\dfrac{1}{1 - (\sqrt{\dfrac{2}{3}} \cos(\dfrac{\pi}{n}))^3})

Let j ( n ) = n 2 3 π sin ( 2 π n ) j(n) = \dfrac{n}{2\sqrt{3}\pi} \sin(\dfrac{2\pi}{n})

Using the inequality: cos ( x ) < sin ( x ) x < 1 \cos(x) < \dfrac{\sin(x)}{x} < 1 \implies

cos ( 2 π n ) < n 2 π sin ( 2 π n ) < 1 1 3 cos ( 2 π n ) < j ( n ) < 1 3 lim n j ( n ) = 1 3 \cos(\dfrac{2\pi}{n}) < \dfrac{n}{2\pi} \sin(\dfrac{2\pi}{n}) < 1 \implies \dfrac{1}{\sqrt{3}} \cos(\dfrac{2\pi}{n}) < j(n) < \dfrac{1}{\sqrt{3}} \implies \lim_{n \rightarrow \infty} j(n) = \dfrac{1}{\sqrt{3}}

lim n V c ( n ) \implies \lim_{n \rightarrow \infty} V^{*}_{c}(n) = 3 V s ( 1 ) 3 3 2 2 \dfrac{3 * V_{s}(1)}{3\sqrt{3} - 2\sqrt{2}} and lim n V s ( n ) \lim_{n \rightarrow \infty} V^{*}_{s}(n) = 3 3 V s ( 1 ) 3 3 2 2 \dfrac{3 \sqrt{3} * V_{s}(1)}{3\sqrt{3} - 2\sqrt{2}} \implies

lim n V c ( n ) V s ( n ) \lim_{n \rightarrow \infty} V^{*}_{c}(n) * V^{*}_{s}(n) = 9 3 V s ( 1 ) 2 ( 3 3 2 2 ) 2 \dfrac{9\sqrt{3} * V_{s}(1)^2}{(3 \sqrt{3} - 2\sqrt{2})^2}

Letting V s ( 1 ) = 1 lim n V c ( n ) V s ( n ) V_{s}(1) = 1 \implies \lim_{n \rightarrow \infty} V^{*}_{c}(n) * V^{*}_{s}(n) = 9 3 ( 3 3 2 2 ) 2 = 2.78061 \dfrac{9\sqrt{3}}{(3\sqrt{3} - 2\sqrt{2})^2} = \boxed{2.78061}

Using right circular cones:

From above the volume of the n n -gonal prism is V c ( n ) = n 2 sin ( 2 π n ) r 2 H V_{c}(n) = \dfrac{n}{2} \sin(\dfrac{2\pi}{n}) {r^{*}}^2 H

Using the inequality cos ( x ) < sin ( x ) x < 1 cos ( 2 π n ) < n 2 π sin ( 2 π n ) < 1 π cos ( 2 π n ) < n 2 sin ( 2 π n ) < π \cos(x) < \dfrac{\sin(x)}{x} < 1 \implies \cos(\dfrac{2\pi}{n})< \dfrac{n}{2\pi} * \sin(\dfrac{2\pi}{n}) < 1 \implies \pi * \cos(\dfrac{2\pi}{n}) < \dfrac{n}{2} \sin(\dfrac{2\pi}{n}) < \pi

lim n V c ( n ) = π r 2 H = V c y l i n d e r \implies \lim_{n \rightarrow \infty} V_{c}(n) = \boxed{\pi {r^{*}}^2 H = V_{cylinder}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...